Metabolic inflammation and immunomodulation in dairy cows - Yuan, Kai (Kansas State University, 2014)
The transition period in dairy cows is characterized by dramatic increases in nutrient requirements for lactation and substantial metabolic stress. The disturbed metabolic balance, coupled with suppressed immune function, contributes to markedly elevated incidence of health disorders. Several lines of evidence suggest that increased inflammation is common during the transition period. Unlike the classical inflammation associated with acute infection, the postpartum inflammatory state is low-grade and often of metabolic origin. This metabolic inflammation plays a key role in numerous disorders; an improved understanding of inflammatory pathways in transition cows may improve our ability to predict and prevent disorders. To mimic metabolic inflammation, in Experiment 1, we administered low amounts of recombinant bovine tumor necrosis factor-α (rbTNFα), a pro-inflammatory cytokine, to early lactation cows, and evaluated whether rbTNFα affects milk production, metabolism, and health. We found that rbTNFα administration increased systemic inflammation, decreased feed intake and milk yield, and increased incidence of disorders. Conversely, preventing excessive inflammation has the potential to improve productivity and health of dairy cows. To identify nutritional strategies that could enhance metabolism and immunity, we evaluated the efficacy of several feed additives. In Experiment 2, we evaluated effects of chromium propionate, rumen-protected lysine and methionine, or both on metabolism and immunity in lactating dairy cows, and found that supplementation of these nutrients may enhance neutrophil function. In Experiment 3, we determined whether supplementation of yeast product to transition cows could enhance production, metabolism, and immunity, and found that yeast product modulated feeding behavior, metabolism, immunity, and uterine inflammation. Overall, a greater understanding of the role of metabolic inflammation in the transition period and the nutritional strategies that could modulate these signals may improve the production and health of dairy cows.
Keywords: Dairy cow; Inflammation; Tumor necrosis factor; Chromium; Yeast; Immunity; Animal Diseases (0476); Animal Sciences (0475); Biology, Animal Physiology (0433)